Semantic Web services, processes and applications and Semantic Web and semantic Web services - Laura Cristina Simões Viana (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2009)
New York, Springer, 2006 ISBN 978-0387302393 USA, Chapman & Hall/ CRC, 2007 ISBN 978-1584889335